STUDI TENTANG PELAKSANAAN PEMBELAJARAN PRAKARYA SUB MATERI KERAJINAN DI KELAS X SMA ADABIAH 2 PADANG - KARMILA, Yofita Sandra, S.Pd. M.Pd. (Serupa The Journal of Art Education, 2019)
The Formulation of the problem in this research is how the Implementation of Craft Sub Craft Material Learning in Adabiah 2 School Class Padang. This research is a qualitative descriptive study. Which is knowing the Implementation of Class X Craft Sub Adabiah 2 Padang. The method used by the teacher is Problem Basic learning, a Method in Which the teacher provides learning to students related to real problems as a context for student more critical thinking and problem solving skills and gaining knowledge. The media used by teachers in the Implementation of Workshop Learning uses elektronik media such as LCD Projectors, while also using online media such as Smartphone.Keywords: Implementation, Methods, Media, Crafts.